If you can't join them, just write about them. - Collins, Michael (Times Higher Education Supplement, 2006)
Relates an experience in defending one's desire to enter a doctorate degree in creative writing. Issues raised between the relation of computer programming and that of teaching; Factors that contributed to his failure to be involve in the teaching career; Advantages of being tenured in creative writing.